Pengaruh Pemberitaan Surat Kabar Kompas, Seputar Indonesia dan Media Indonesia Terhadap Persepsi Masyarakat Pengguna Tabung Gas - Arief Fajar; Dwi Yunita Restivia (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
The objectives of this research are (1) to describe the influence of newspaper report on the perceptions of users cylinders gas in RW 003 Margajaya Bekasi; (2) to what extend the influence of newspaper coverage of the perception of users of cylinders gas in the RW 003 Margajaya Bekasi. The study concludes that (1) newspaper report has significant influence in a positive direction toward perception of users of cylinders gas in RW 003 Margajaya South Bekasi; (2) newspaper news has affected perception of users of cylinders gas by 59%. It means whenever there is increase in newspaper coverage, then the perception of the user who use cylinders gas is getting better.